Die Fläche. (Wien : Verlag Anton Schroll & Co, 1903)
Die Fläche (The Surface) was a Viennese graphic arts periodical published in two volumes featuring the work of artists associated with the Wiener Werkstätte- Bertold Löffler, Moriz Jung, Franz Karl Delavilla, Urban Janke, Wenzel Oswald, Gustav Marisch, Karl Schwetz, and others. The first volume was published in 1903/1904 by Felician Baron Myrbach and the second in 1910 by Bertold Löffler in association with Anton Scholl & Co.They contained a total of 124 pages of contemporary applications of graphic design with examples of poster art, books, wallpaper, textiles, stained glass, inlay, embroidery, monograms, business cards, and costume jewelry.(theviennasecession.com)
Facsimile. 2023
Online: https://www.theviennasecession.com/die-flache
Duits
Tijdschriften
Keywords: 1902 - 1911.; 20ste eeuw; Wiener Sezession; typografie; Wenen